Abolition of Landlordism in Kerala A Redistribution of Privilege - Ronald J Herring (ECONOMIC AND POLITICAL WEEKLY, 1980)
The Kerala land reforms which came into effect on the first day of 1970 have been virtually com-pleted during the decade. Widely hailed as a model, the reforms have in fact been relatively well implemented and effect a substantial redistribution of privilege, but stop considerably short of establishing 'land to the tiller', as is often claimed.The privilege of obtaining income (and security) from land ownership independent of labouring on the land has been transferred, and on a significant scale, but not abolished; the rents of rentiers have been abolished, but not the profits of capitalist landowners, who may or may not be functionally absentee. The major beneficiaries of the abolition of landlordism have been rich peasants, not poor peasants or agricultural labourers. The major reasons for this result lie in the conceptualisation, rather than lapses in implementation, of the reform measures, most importantly the uniform treatment of all tenant-landlord relations as 'feudal' rather than a recognition of tenancy as a privileged property form on most of the leased area in the state and the treatment of the problems of agricultural labourers as those of a rural proletariat rather than as those of an aspiring peasantry-to-be.